Nurses’ Role in Strengthening Sensory Inputs of Preemies in NICU - Renilda Shanthi Lolo; Theresa Leonilda Mendonca (RGUHS Journal of Nursing Sciences)
Infants born prematurely are deprived of the prenatal sensory stimulation necessary for their proper development and the harsh environment in neonatal intensive care unit NICU severely impacts their growth. This paper aims to strengthen the mother-newborn interaction to promote healthy growth and development by implementing evidenced-based sensory care in NICU and thus reducing the newborn mortality rate. This paper is focused on the initiation of positive sensory inputs for the preemies in the NICU based on evidence-based care to promote in-utero experience to the preterm newborn. The main sensory inputs include Octopus therapy therapeutic positioning and nesting and multisensory stimulation including auditory tactile vestibular and visual stimulations. The research studies have shown the benefits of sensory stimulation of preterm newborns in NICU in terms of growth of the child neuromotor development physiological stability improvement in sleep and improved mother-newborn interaction promoting adjustment of the newborn to the extrauterine life. Nurses play a very important role in initiating this sensory stimulation for the preemies admitted to NICU with maternal participation in care.